PERAN GURU BK DALAM MENINGKATKAN RASA INGIN TAHU (CURIOSITY) PADA SISWA MENGGUNAKAN BIMBINGAN KLASIKAL - Alyana, Adinda Ayu; Astuti, Budi (Universitas Muria Kudus, 2024)
Character strength is the basis of our identity, it can be seen when we express this strength of character through thoughts and actions. The truly wonderful thing about character strengths is that they can contribute to personal well-being, the quality of relationships, and the personal community as a whole. For example, curiosity helps explore new ideas, people, places and so on. As well as making it possible to collaborate on projects and see the value of each person's contribution and the courage to help yourself get out of your comfort zone, and be able to challenge yourself. Therefore, the role of the guidance and counseling teacher is very important in increasing students' curiosity, especially in terms of education, which shows that we tend to feel happier, more connected, and more productive. Counseling teachers teach students to always have a high curiosity by exploring new things, creating new ideas, and always generating new innovations.